2020
DOI: 10.1080/13880209.2020.1806335
|View full text |Cite
|
Sign up to set email alerts
|

Fengbaisan suppresses endoplasmic reticulum stress by up-regulating SIRT1 expression to protect rats with chronic obstructive pulmonary diseases

Abstract: , San-gai Pan , Xiao-ping Ge & Xing-ping Dai To cite this article: Yu Wang , Nan-xiang Su , San-gai Pan , Xiao-ping Ge & Xing-ping Dai (2020) Fengbaisan suppresses endoplasmic reticulum stress by up-regulating SIRT1 expression to protect rats with chronic obstructive pulmonary diseases,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…It has been reported that more than 3 million people die of COPD worldwide, accounting for 6% of all deaths ( 55 ). Moreover, COPD can further develop into pulmonary heart disease and respiratory failure ( 117 ), so it is of great significance to find a better treatment strategy for COPD. Zhou et al ( 118 ) reported that oxidative stress, inflammation, and apoptosis were considered the most important influential factors for COPD occurrence.…”
Section: Multitasking Roles In Respiratory Diseasesmentioning
confidence: 99%
“…It has been reported that more than 3 million people die of COPD worldwide, accounting for 6% of all deaths ( 55 ). Moreover, COPD can further develop into pulmonary heart disease and respiratory failure ( 117 ), so it is of great significance to find a better treatment strategy for COPD. Zhou et al ( 118 ) reported that oxidative stress, inflammation, and apoptosis were considered the most important influential factors for COPD occurrence.…”
Section: Multitasking Roles In Respiratory Diseasesmentioning
confidence: 99%
“…Dioscorea oppositifolia L. DIOSCOREACEAE India, Sri Lanka, Bangladesh, Birmania Shan yao, batata china Rizomas secos fragmentados envasados Asma, tos, disnea, bronquitis crónica, enfermedad pulmonar obstructiva crónica. Antiinflamatorio, protector pulmonar, inmunomodulador (Wang et al, 2020b). Antitusivo, antiséptico del tracto respiratorio superior (Barth et al, 2015;Hurrell y Puentes, 2017).…”
Section: Asteraceae China Ju Hua Crisantemo Inflorescencias Secas Fra...unclassified
“…Ophiopogon japonicus (Thunb. ) Antitusivo, antiinflamatorio, inmunomodulador, protector pulmonar, antimicrobiano (Chen et al, 2016;Yao et al, 2019;Wang et al, 2020b).…”
Section: Nelumbo Nuciferaunclassified
“…UPR activation was also detected in animal models of CS-induced COPD. Increased protein and mRNA expression levels of CHOP and GRP78 were detected in the lung tissues of COPD rats [ 117 , 118 ]. Long-term exposure to CS also increased the expression levels of the GRP78, ATF4, ATF6, and CHOP proteins and the phosphorylation of PERK and IRE1 in the lung tissues of mice [ 12 ].…”
Section: Copd and Er Stressmentioning
confidence: 99%
“…As previously described, all three UPR branches cause inflammatory responses. Significant ER stress was observed in the lung tissues of CS-induced COPD animal models, with elevations in the total inflammatory cell levels and neutrophil percentages in the bronchoalveolar lavage fluid and significantly increased levels of the inflammatory factors IL-6, IL-8, and TNF-α [ 12 , 118 ]. CS stimulation also activates the NLRP3 inflammasome, which promotes the secretion of IL-1β and IL-18 in the lung tissue [ 129 ].…”
Section: Copd and Er Stressmentioning
confidence: 99%